Forestry Interventions for Ganga Rejuvenation: A Geospatial Analysis for Prioritizing Sites - Savita, P. K.; Mathur; Sharma, Lalit Kumar; Kumar, Manoj (Indian Forester, 2019)
The river Ganga is the most sacred river and lifeline to millions of Indians. Ganga River has always attracted various groups of people, be it a common man, researcher, philosopher or religious person. Ganga represents one of the most fascinating, complex and dynamic river ecosystems on the planet earth. It's more than just a river and has now become one of the priority concern for ensuring ecological integrity and preserving natural sanctity. Rapid population growth and economic activities directly influencing the river have significantly influenced the extent and the quality of river water. Attempts have been made by the Government of India in recent past to rejuvenate the river to its pristine state. Although there can be various scientific and technical interventions yet natural ways of treating the river could be one of the sustainable options for rejuvenation. Forestry interventions are such promising solutions, though, the question arises as to what are the priority sites for such interventions. The present study demonstrates use of modern tools of remote sensing and geographical information system (GIS) for the identification of priority sites to implement the forestry interventions intended for river Ganga rejuvenation.